Graduation approach to poverty reduction in the humanitarian context: Evidence from Bangladesh - Rahman, Atiya; Bhattacharjee, Anindita; Nisat, Rafia; Das, Narayan (Wiley, 2024)
This article was published in The Journal of International Development [©2023 Rights managed by Wiley] and the definite version is available at: https://doi.org/10.1002/jid.3728 The Article's website is at: https://onlinelibrary.wiley.com/doi/10.1002/jid.3728